DEMOCRATIZING LOCAL GOVERNMENT: WHAT MALAYSIA CAN LEARN FROM MEXICO AND INDIA (Journal of International Studies, 2020)
The Pakatan Harapan 2018 election manifesto had established commitments to strengthen the authority of local government, and to make local councils more accountable. This suggested that the local government elections would resume, after an absence of more than 60 years. While the Pakatan Harapanâ€™s tenure as Malaysiaâ€™s ruling government was short-lived, their rise to power did put the local government back into the spotlight, as well as elevated the prospects of the resumption of local government elections in the country. There are a number of reasons that supports a more democratic and participatory approach to local government which has been highly hoped for in Malaysia. These include the view that it discourages public malfeasance and produces local officials that are more responsive to the needs of the citizens they serve. However, there are challenges that follow with the introduction of a more democratic form of local government, especially for countries that are attempting to transition from authoritarianism to a democracy at the national level, and contain a diverse multi-ethnic population of differing socio-economic backgrounds.  In order to better understand what these challenges are and how they can be overcome, this study examines two case studies, Mexico and India. These two countries have shown some similarities to Malaysia, particularly with regards to regime-type and demographics. This study considers the evolving approach taken by these two countries on their local government, in terms of their structure and practices. It is proposed that the case studies could provide potential lessons for Malaysia. This study begins with a brief historical overview of the system of local government in Malaysia to present day. This is followed by a discussion of the uneven experiences of Mexico and India on the efforts to democratize their local governments. The findings from the examination of both the case studies reveal the manner for which the countries with an authoritarian past often undergo during a transitional period, whereby although the structures of local governance have become more democratic, local officials and citizens are remain trapped in the old authoritarian modes of behavior. Unless interventionist steps are taken, democratizing local government structures alone do not necessarily lead to greater citizen empowerment, especially for those from the more marginalized sections of society.